Titik Temu Transpersonal Psychology dan Tasawuf - Khadijah, Khadijah (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article aims to introduce transpersonal psychology approach, especially its meeting point with the world of Sufism in Islam. The article tries to answer the following questions, are: 1) what is the difference between transpersonal psychology and other psycho-logical theories, and; 2) in what aspect transpersonal psychology shares a common ground with Sufism? The writer finds that there is a significant difference between transpersonal psychology and other psychological theories, especially psychoanalysis and behaviorism. Psychoanalysis emphasizes the deepest meaning of human behavior with a tendency to override the meaning of physical aspect. Behaviorism has been strongly influenced by pure science. In fact, research on the human psyche aspect cannot be done simply by applying pure science. Meanwhile, transpersonal psychology tries to fundamentally reinforce and develop human potential, both physical and mental aspects. Moreover, this approach reaches supernatural and spiritual aspects of human beings. The writer tends to argue that the common ground shared by the mystical aspects of the Western world, in the perspective of transpersonal psychology, and Sufism in Islam lays in the fact that each entity puts great emphasis on managing and increasing the spiritual aspect of human. Keywords: transpersonal psychology, tasawuf, common ground.